Медична дипломатія у контексті досягнення цілей сталого розвитку - Карпишин, Наталія; Гесюк, Мар'яна (Тернопіль: ЗУНУ, 2022)
Medical diplomacy is a form of diplomacy for promoting national interests in the field of providing medical care and vaccination of the population.
Keywords: дипломатія, медична дипломатія, вакцинальна дипломатія; diplomacy, medical diplomacy, vaccine diplomacy